Studies of the coronary circulation in Chagas' heart disease - Marin-Neto, José Antonio (1995)
Pathogenesis of chronic Chagas' heart disease may include various disturbances in the coronary circulation, that could be responsible for the myocardial lesions seen in human hearts and in experimental models of the disease. In this paper we critically reviewed the anatomical and functional abnormalities described in chronic chagasic patients, pertaining to the so-called vascular pathogenetic theory of Chagas' disease. The epicardial coronary arteries are usually free of significant obstructive disease in nonselected groups of chagasic patients examined at autopsy or by coronary angiography. However, chagasic patients who were studied after an episode of acute myocardial infarction, show the same patterns of atherosclerotic coronary artery disease seen in the general nonchagasic population. Studies of chagasic patients with angiographically normal coronary arteries, by several scintigraphy methods, revealed myocardial perfusion abnormalities which may be caused by the microcirculatory derangements described in animals experimentally infected with the T. cruzi. Since hypoperfusion has been detected in regions with normal or mildly impaired wall motion, it is likely that the microvascular disturbances precede and may be a causative mechanism for the subsequent myocardial damage. We speculate that hibernating ventricular areas may occur in chagasic patients, on the basis of the evidence gathered from these studies. Recent investigations of chronic patients with Chagas' disease and chest pain showed attenuation of the vasomotor responses to physiological and pharmacological stimuli, in the epicardial coronary arteries.